Beyond BMI: waist circumference and social environment is associated with motor performance ability in kindergartners - Hoffmann, Sascha W.; Dreher, Matthias; Urschitz, Michael S.; Simon, Perikles (BMC pediatrics, 2020)
Background The aim of the current study was to examine the relationship between anthropometric characteristics (i.e. body height, body weight, body mass index [BMI] and waist circumference [WC]) with motor performance ability [MPA], social environmental factors of the district (i.e. employment status/working life, education, social situation/heterogeneity and home environment), where the respective kindergarten was located, as well as other potential health determinants in a representative sample of kindergartners. Methods We analyzed data of 434 children aged 3 to 6 years which were obtained from a community-based cross-sectional health study conducted in the city of Mainz, Germany. Body height and weight, BMI and WC standard deviation scores [SDS] were calculated relative to the international proposed cut-offs of the IOTF. MPA was collected with multiple test items to determine coordination, speed strength, muscular endurance and speed. The life situation index [LSI] was used to assess the social environment of the district of the kindergarten. Adjusted for covariates, correlation and logistic regression analyses were conducted to estimate the effect of WC on MPA. Results Below-average MPA was found in 46% of the sample. While there was no relationship to BMI (odds ratio [OR]: 1.09, 95% confidence interval [95% CI]: 0.83–1.44; p = 0.538), WC SDS was positively associated with below-average MPA (OR: 1.41, 95% CI: 1.01–1.95; p = 0.041). Further results show that the social environment of the district of the kindergarten was independently related to below-average MPA (OR: 2.72, 95% CI: 1.29–5.75; p = 0.009). Conclusion The findings suggest that WC rather than BMI is linked to measurements of MPA already in kindergartners and furthermore, there seems to be an independent association between MPA and the social environment of the district of the respective kindergarten.